Status of Food Labeling of Soft Beverage According to BFSA Guidelines (Global Journal of Management and Business Research, 2020)
Why should people know about the Labeling of Soft Beverages in Bangladesh? To find the answer to this question, this article has focused on the Food Safety Act, 2013 of Bangladesh, the status of Labeling of Soft Beverage, and customer awareness. The core intent of the study is to examine and analysis the present scenarios of soft beverage labeling according to the #x201C;Regulations of product labeling,#x201D; the Food Safety Act, 2013 (Act No. 43 of 2013) and #x201C;Regulations on the use of additives products,#x201D; (Act No. 43 of 2013), section-87 and section-27. To attain the goal of the research, most important considerable variables and attributes are taken for survey from BFS Act and regulations. The study, descriptive in nature, has been conducted based on primary data. Total 39 criteria (Variable) have been taken related to the Regulations of product labeling and Regulations on the use of additives products. The sample size of the study is 29, where the sample is the labels of soft beverage. The convenience sampling method has been used here where the sample collected from Dhaka, Manikganj, Gazipur district of Bangladesh.
Keywords: food labeling; customer awareness; soft beverage; BFSA; healthy